2012
DOI: 10.1002/cm.21066
|View full text |Cite
|
Sign up to set email alerts
|

G protein regulator 1 (GPR‐1) localizes to cortical sites of artificial mechanical indentation in Caenorhabditis elegans zygotes

Abstract: Cytokinesis and spindle positioning require the cortical force regulator G Protein Regulator 1/2 (GPR-1/2). GPR-1/2 is thought to localize to sites of cortical force generation. Does GPR-1/2 also act as a sensor for mechanical stimulation? I mechanically stimulated the cortex by indenting it with a glass needle and observed the cortical localization of a YFP::GPR-1 transgene. I found that cortical YFP::GPR-1 accumulated at the site of mechanical indentation. This phenomenon occurred on most of the cortical are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In C. elegans, microtubule-based pulling forces are controlled by a ternary complex consisting of G alpha proteins, LIN-5, and G-protein regulator 1 and 2 (GPR-1/2), which are two nearly identical regulators. GPR-1/2 has been shown to be required for force generation and potentially also force sensing to achieve spindle positioning and cytokinesis [6][7][8][9][10][11] . The concentrations of GPR-1/2 are crucial determinants for microtubule-based pulling forces, as GPR-1 knockdown leads to reduced forces and GPR-1 overexpression leads to increased pulling forces in a dose-dependent manner 12,13 .…”
mentioning
confidence: 99%
“…In C. elegans, microtubule-based pulling forces are controlled by a ternary complex consisting of G alpha proteins, LIN-5, and G-protein regulator 1 and 2 (GPR-1/2), which are two nearly identical regulators. GPR-1/2 has been shown to be required for force generation and potentially also force sensing to achieve spindle positioning and cytokinesis [6][7][8][9][10][11] . The concentrations of GPR-1/2 are crucial determinants for microtubule-based pulling forces, as GPR-1 knockdown leads to reduced forces and GPR-1 overexpression leads to increased pulling forces in a dose-dependent manner 12,13 .…”
mentioning
confidence: 99%
“…A special class of MAPs, which connect cMTs and PM, is very important for PC shape formation (Bringmann, 2012; Liu et al, 2016; Sugiyama et al, 2017; Oda, 2018). These MAPs sense the cell wall components, hormones, and polarized PM signaling in shaping the interlocking PCs (Barton et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…) (Gusnowski and Srayko, ). GPR‐1 is also known to sense and respond to the mechanical properties of the cortex, which may be important for its role in spindle positioning (Bringmann, ). Laser‐severing experiments have additionally shown that the pulling forces in the posterior end of the cell are stronger than those found in the anterior, resulting in spindle displacement from a central location (Grill et al, ; reviewed in Gillies and Cabernard, ).…”
Section: The C Elegans Embryo: a Model For Polarity‐dependent Spindlmentioning
confidence: 99%